Spinal-pelvic orientation: potential effect on the diagnosis of spondyloarthritis. (24th June 2019) - Carvajal Alegria, Guillermo; Deloire, Lucile; Herbette, Marion; Garrigues, Florent; Gossec, Laure; Simon, Alexandre; Feydy, Antoine; Reijnierse, Monique; van der Heijde, Désirée; Loeuille, Damien; Claudepierre, Pascal; Marhadour, Thierry; et al.
Abstract: Objective: To assess associations of spinal-pelvic orientation with clinical and imaging-study findings suggesting axial SpA (axSpA) in patients with recent-onset inflammatory back pain. Methods: Spinal-pelvic orientation was assessed in DESIR cohort patients with recent-onset inflammatory back pain and suspected axSpA, by using lateral lumbar-spine radiographs to categorize sacral horizontal angle (<40° vs ⩾40°), lumbosacral angle (<15° vs ⩾15°) and lumbar lordosis (LL, <50° vs ⩾50°). Associations between these angle groups and variables collected at baseline and 2 years later were assessed using the χ 2 test (or Fisher's exact) and the Mann–Whitney test. With Bonferroni's correction, P < 0.001 indicated significant differences. Results: Of 362 patients, 358, 356 and 357 had available sacral horizontal angle, lumbosacral angle and LL values, respectively; means were 39.3°, 14.6° and 53.0°, respectively. The prevalence of sacroiliitis on both radiographs and MRI was higher in the LL < 50° group than in the LL ⩾50° group, but the difference was not statistically significant. Clinical presentation and confidence in a diagnosis of axSpA did not differ across angle groups. No significant differences were identified for degenerative changes according to sacral horizontal angle, lumbosacral angle or LL. Conclusion: Spinal-pelvic balance was not statistically associated with the clinical or imaging-study findings suggesting axSpA in patients with recent-onset inflammatory back pain.